Endodontic Retreatment In Case Of Failure: Case Report - Kevin Prayogo; Dian Agustin Wahjuningrum; Ari Subiyanto (Conservative Dentistry Journal, 2019)
Background: In medical practice, clinicians come across a lot of obstacle during a treatment , that can lead to a failure, like other dental treatments, endodontics too can fail. Inappropriate mechanical debridement, persistence of bacteria in the canals and apex, poor obturation quality, over and under extension of the root canal filling, and coronal leakage are some of the commonly attributable causes of failure. Despite the high success rate of endodontic treatment, failures do occur in a large number of cases and most of the times can be attributed to the already stated causes. Purpose: Endodontic retreatment of a failure is required by the increased desire to preserve the tooth on the dental arch, preventing the need for dental extraction that may have adverse consequences in terms of functional and psychological effect on patients. Case: This article presents a case report about dental retreatment with 2 common failure, that was under filling obturation and non-fit post. Case management: The failure was corrected with endodontic retreatment, and finally restored with fiber post and porcelain fused to metal crown. Conclusion: Endodontic retreatment was done successfully on underfilling obturation and non-fit post. The patient was satisfied with the result.